ANALISIS KUALITAS PELAYANAN DAN CITRA MEREK TERHADAP KEPUASAN PELANGGAN MELALUI KEPUTUSAN PEMBELIAN PADA EKSPEDISI JNE EXPRESS - Muhammad Dafa, (2022)
This research was conducted by researchers as quantitative research to determine the effect of service quality and brand image on purchasing decisions, the influence of purchasing decisions, brand image and service quality on customer satisfaction, as well as the influence of service quality and brand image indirectly on customer satisfaction through purchasing decisions. The data collection carried out by this study was an online questionnaire. This study uses the SEM method with the software used is SmartPls 3.0. Service quality has a positive and significant effect on customer satisfaction with an original sample value of 0.346. Brand image has no positive and significant effect on customer satisfaction with an original sample value of 0.125 Keywords: Service Quality; Brand Image; Buying Decision; Customer Satisfaction